Conjoint analysis of nitrogen and phosphorus metabolism in urban system: A case study of Dar es Salaam, Tanzania - Zheng Guo; Sophia Shuang Chen; Chuanhe Xiong; Anna Charles Mkumbo; Qun Gao; Qiushi Shen; Giri R. Kattel (Journal of Industrial Ecology, 2024)
Nitrogen (N) and phosphorus (P) metabolism is becoming an increasingly complex process during urbanization due to increasing rates of consumption and emission worldwide. Understanding the urban N and P metabolism helps identifying production capacity, consumption demand, and the impact of N and P emissions on the environment, providing a scientific basis for decision‐making in sustainable utilization of N and P resources. Quantifying and mapping the source, path, and sinks of N and P in an urban system is the premise of controlling emissions. In this paper, we used the substance flow analysis (SFA) method to describe the N and P metabolism processes in the urban system of Dar es Salaam (Tanzania) in 2017, and used the scenario‐based analysis method to understand the impact of different N and P metabolisms on potentially recoverable N and P sources by 2030. The results showed that the urban system of Dar es Salaam receives a total input flow of 28,101.8 tN/year and 3,379 tP/year, with a total output flow of 18,859.6 tN/year and 1,849.3 tP/year with net stock changes of 9,242.2 t/year for N and 1,529.7 t/year for P, respectively. We noticed that increased human activities largely represented the city's waste released after the household consumption, and would become the main causes of N and P emissions. In addition to this, 59.38%, 31.25%, and 9.38% of N flow quantification quality were at high, medium, and low levels, respectively, while 74.07%, 11.11%, and 14.81% of P flow quantification quality were at high, medium, and low levels, respectively. Our results suggest that implementing integrated nutrient management measures, such as changes in people's diets and the use of washing products, and improved management and technologies of manure, sewage, and landfill leachate treatment, would be the most effective approach to resolve the urban nutrient emissions in Dar es Salaam.